#TITLE_ALTERNATIVE# - Achmad (NIM 202 03 007), Rahim
Abstract: The groundwater flow pattern of Curug Dago river zone in northern Bandung was constructed by combining multiple geophysical methods which were: DC resistivity sounding, ground penetrating radar (GPR), and geomagnetism using finite-difference numerical modeling. The above geophysical methods revealed that basically the structure beneath the area consists of three layers of rock which are comparable with the previous geological and hydrological parameter studies. An upper layer sediment, associated with clay (sandy clay and clayed tuff) and has relatively low permeability overlays a lower sediment of tuff and. breccia above the third layer of massive volcanic breccia. The numerical modeling was carried out using a conceptual model approach based on all available data. Quantitatively the water table distribution, flow regime, leakage rates between aquifers, groundwater mass balance and other aquifer hydraulic properties can be analyzed from the modeling results. Both hydraulic gradient and geological structure seem to dictate the groundwater flow in the area. This study may have urgencies as vv ell as practical implications regarding the recent available groundwater database of the area. and future possibilities of groundwater management and development.